Behçet's disease and factor V Leiden: A thrombogenic synergy causing budd-chiari syndrome - Ameer Awashra; Zaid Sawaftah; Salsabeel Bishawi; Aseel Eid; Aya Milhem; Dawoud Hamdan; Ali Bani Odah; Ahmad Sawafta; Jehad Khamaysa; Yazan Ghannam; Hadi Rabee (Radiology Case Reports)
Behçet's Disease (BD) is a multisystem inflammatory disorder that can lead to severe vascular complications, including Budd-Chiari Syndrome (BCS), a rare but life-threatening condition characterized by hepatic vein obstruction. The co-occurrence of BD and inherited thrombophilia, such as Factor V Leiden mutation, significantly increases the risk of thrombosis, complicating the clinical management of affected individuals. In this case, a 16-year-old female initially presented with nonspecific symptoms of generalized fatigue and bone pain, which later progressed to abdominal distension and significant hepatosplenomegaly. Imaging and further diagnostic evaluation confirmed BCS as the initial manifestation of BD, a rare but severe complication. Genetic testing revealed a heterozygous mutation for Factor V Leiden and the presence of the HLA-B51 allele, highlighting a thrombogenic synergy between BD and inherited thrombophilia. Aggressive anticoagulation therapy was initiated, resulting in partial recanalization of the hepatic veins and stabilization of the patient's condition. This case emphasizes the need for early consideration of BCS in BD patients, especially in those with concurrent prothrombotic disorders, as timely intervention is crucial for improving clinical outcomes. The interplay of autoimmune and genetic factors in this case provides valuable insights into the complex pathophysiology and management of BCS associated with BD.